Secretion of tumor necrosis factor and reactive oxygen intermediates from soluble antigens of Plasmodium falciparum stimulated-peritoneal mouse macro-phages - Mahardika Agus Wijayanti Mahardika Agus Wijayanti (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1999)
Background: Malarial infection is stil one of major health problems in the world. In Indonesia, malarial infection is especially caused by Plasmodium falciparum and Plasmodiun vivax. Host immune responses to malarial infection are complex mechanisms, including the humoral immunity by antibody and cellular immunity by T cells and activated effector cells. Macrophages as an effector cells kill malarial parasite by oxidative and non-oxidative mechanism. Tumor necrosis factor (TNF) and reactive oxygen intermediates (ROI) are mediators produced by macrophages which represent as non-oxidative and oxidative killing respectively.Objectives: Understanding the secretion ability of tumor necrosis factor and reactive oxygen intermediates from soluble antigens of P. falciparum stimulated-peritoneal mouse macrophages.Method: In this. study, soluble antigens of P. fa/p/parum stimulated-peritoneal mouse macrophages were tested to produce TNF and ROI in vitro. Secretion of TNF was measured by MTT assay dan ROI by NBT reduction assay. Swiss mice were divided into two groups of 15 mice each. One group was stimulated by soluble antigens as experimental group and the other as control group.Result: Secretion of TNF and ROI by soluble antigens of P. falciparum stimulated-peritoneal mouse macrophages were significantly higher (p<0,01) than control group.Conclusion: Soluble antigens of P. falciparum could activate mouse peritoneal cells in vivo. Therefore, mouse macrophages provide a convenient system for investigating the human malarial soluble antigens.Key. words : Soluble antigens of Plasmodium fa/ciparum - Cellular Immunity - Macrophages – Tumor - Necrosis Factor - Reactive Oxygen Intermediate